2020
DOI: 10.21203/rs.3.rs-100715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-Transplant Donor HBV DNA+ and Male Recipient are Independent Risk Factors for Treatment Failure in HBsAg+ Donors to HBsAg- Kidney Transplant Recipients

Abstract: Background: In order to lighten the burden of organ shortage around the world, using potential infectious donor might be an option. However, scarce evidences have been published on Kidney transplantation (KTx) from hepatitis B surface antigen (HBsAg)+ donors to HBsAg- recipients [D(HBsAg+)/R(HBsAg-)] without hepatitis B virus (HBV) immunity. Here, we reported the results of D(HBsAg+/HBV DNA- or +)/R(HBsAg-) living KTx recipients with or without HBV immunity.Methods: We retrospectively identified 83 D(HBsAg+)/R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, this was not supported by the HBV serological data in our patient, in whom HBVr occurred in the presence of a high pre-existing anti-HBs antibody titre, which gradually increased to 951.36 mIU/ml after reactivation. Wang et al [ 15 ] reported increases in the post-transplant anti-HBs titres in HBsAg-negative renal transplant recipients who received a kidney from an HBsAg-positive donor. The authors speculated that HBsAg stimulation was similar to HBV “vaccination”.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not supported by the HBV serological data in our patient, in whom HBVr occurred in the presence of a high pre-existing anti-HBs antibody titre, which gradually increased to 951.36 mIU/ml after reactivation. Wang et al [ 15 ] reported increases in the post-transplant anti-HBs titres in HBsAg-negative renal transplant recipients who received a kidney from an HBsAg-positive donor. The authors speculated that HBsAg stimulation was similar to HBV “vaccination”.…”
Section: Discussionmentioning
confidence: 99%